Internacionalização, humanismo e ética (Orfeu, 2019)
I offer some considerations regarding the internationalization process in Brazilian public universities. The focus of this discussion is the internalization of graduate programs. The ordinary expected outcomes from an international cooperation are inquired. Following, I purpose a rethinking of internationalization process in the light of a humanistic perspective. This proposition is based on my experience as a coordinator of projects of international collaboration. In a humanistic point of view, interpersonal relationships are enhanced and also intended as outcomes from inter-institutional cooperation. The expected result with the adoption of this humanist approach is the ethical transformation of the participants in experiences of academic mobility.
Keywords: internationalization; humanism; honesty expectation; ethics